2009
DOI: 10.1590/s0004-282x2009000300016
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychomotor development before and after open-heart surgery in infants

Abstract: -There are few Brazilian studies on neuropsychomotor follow-up after open-heart surgery with circulatory bypass in infants. Twenthy infants had neurodevelopmental outcomes (neurological exam and Denver II test) assessed before open-heart surgery, after intensive care unit discharge and 3-6 months after hospital discharge. Heart lesions consisted of septal defects in 11 cases (55%). The mean circulatory bypass time was 67±23.6 minutes. Fifteen infants had altered neurological examination and also neurodevelopme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Preoperative features of neurodevelopmental delay described in neonates and infants with CHD include seizures, hypotonia, hypertonia, motor asymmetry, inability to suck, feeding difficulties, cranial nerve abnormalities, lethargy, restlessness, agitation and autistic features. These abnormalities are more common in cyanotic infants with oxygen saturation of < 85%.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative features of neurodevelopmental delay described in neonates and infants with CHD include seizures, hypotonia, hypertonia, motor asymmetry, inability to suck, feeding difficulties, cranial nerve abnormalities, lethargy, restlessness, agitation and autistic features. These abnormalities are more common in cyanotic infants with oxygen saturation of < 85%.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 20 infants evaluated, 15 had altered neurological examination and developmental delay before surgery, whose normalization was observed only six months after the procedure in six participants. The authors concluded that after five months on average, the frequency of surgery was reduced among children with Denver II "suspect" delay from 75% to 55% [ 19 ] .…”
Section: Discussionmentioning
confidence: 99%
“…Studies included in this review originated from 5 continents. Sixteen (35%) studies were conducted in the United States, 15-30 7 (15%) in Canada, 31-37 6 (13%) in Germany, 38-43 4 (9%) in Australia, [44][45][46][47] 2 (4%) in the Netherlands, 48,49 2 (4%) in Switzerland, 50,51 2 (4%) in Finland, 52,53 2 (4%) in Japan, 54,55 1 (2%) in Brazil, 56 1 (2%) in India, 57 and 1 (2%) in Norway. 58 In addition, 2 (4%) studies were conducted in centers located both in Canada and the United States.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…In this study, the authors reported a 20.0% prevalence of motor skill difficulties. 21 Additionally, da Rocha et al 56 reported suspected delays in 55.0% of infants with CHD on the basis of the results of a screening test. The prevalence of severe motor impairments (,22 SD) in infants with CHD ranged from 0.0% to 54.6% (IQR: 8.4%-50.9%).…”
Section: Motor Skills Across Agesmentioning
confidence: 99%